EDUKASI PAGUYUBAN JARAN KEPANG LANGEN TURONGGO JATI GUNA MENDUKUNG DESA WISATA BUDAYA “NGIDAM MUNCAR” KABUPATEN SEMARANG - Paranti, Lesa; Putro, Bintang Hanggoro; Wiyoso, Joko; Salafiyah, Nafik; Fabiyanto, Enggan; Khamdani, Muhammad (Riau Journal of Empowerment, 2023)
"Ngidam Muncar" is a culture-based tourism village located in Muncar Village, Susukan District, Semarang Regency. Muncar has the Jaran Kepang Langen Turonggo Jati (LTJ) community which has so far contributed to strengthening tourism potential in Muncar, however based on the findings there are problems including: 1) lack of regeneration of Jaran Kepang dancer cadres; 2) lack of human resources in terms of understanding and skills in Jaran Kepang dance because they are self-taught; 3) have not been able to wear fashion make-up independently. This problem is urgent to be resolved immediately because currently tourism in Muncar Village has started to revive after yesterday's hiatus due to the Covid 19 pandemic. The program implementation method starts with FGD, training for 5 meetings and evaluation. The results of the activities that have been carried out include 1) forming a cadre of 20 young people and youngsters; 2) participants have basic dance knowledge and movement skills; 3) participants have the knowledge and skills to wear fashion make-up independently. The conclusion of this activity program is that there is an increase in the understanding and skills of the participants. These skills will get better if honed continuously.